CLINICAL MANAGEMENT OF CANINE PARVOVIRAL ENTERITIS IN A 3-MONTH-OLD LHASA APSO IN ABUJA, FCT, NIGERIA - Godwin, Enid; Ajogi, Donken I.; Enem, Simon I.; Abdullahi, Sa’adatu I.; Dauda, Jamila; Muktar, Sabuwa A.; Egwu, Godwin O.; Attah, Omerah Raphael; Galadima, Lami (FUDMA Journal of Sciences, 2025)
Canine parvovirus (CPV) is a highly contagious, non-enveloped, single-stranded DNA virus of the Parvoviridae family that primarily affects rapidly dividing cells in the intestinal crypts and bone marrow of dogs. This report describes the clinical presentation and successful management of a 3-month-old female Lhasa Apso puppy presented to the Police Veterinary Hospital, Garki, Abuja, with hemorrhagic diarrhea and frothy vomiting. Diagnosis was confirmed using a rapid parvoviral antigen test kit. Hematological findings revealed leukocytosis (18.0 × 10⁹/L) and lymphocytosis (7.3 × 10⁹/L), suggestive of a viral infection. The treatment protocol included fluid therapy, antimicrobial coverage, antiemetics, vitamins, activated charcoal, and oral protectants. Clinical improvement was observed within five days of intensive management, with full recovery and discharge on day five. This case underscores the importance of early diagnosis, aggressive supportive therapy, and strict adherence to vaccination schedules for effective prevention of parvoviral enteritis in puppies.